DEVELOPMENT OF E-MODULE BASED ON PROBLEM BASED LEARNING (PBL) IN HYDROCARBON MATERIAL - Tsurayya Zhafirah; Maria Erna; R Usman Rery (STAI Hubbulwathan Duri, 2020)
This study aims to develop e-module based on Problem Based Learning (PBL) on hydrocarbon materials using the Kvisoft Flipbook Maker application. This research is a development research with 4-D development model. The data obtained came from 6 validators (3 material experts and 3 media experts), 4 chemistry teachers and 12 students from four high schools namely SMA Negeri 8 Pekanbaru, SMA Negeri 5 Pekanbaru, SMA Negeri 3 Pekanbaru and SMA IT Al-Fityah Pekanbaru. Data collection techniques used in the form of documentation and questionnaires. The data analysis technique is by calculating the percentage score of the validation assessment and user responses. The results showed that the e-module developed fulfilled very valid criteria with a percentage of 85.39% by material experts and 97.02% by media experts. The results of the chemistry teacher and student response test showed that the e-module developed fulfilled very practical criteria with a percentage of 92.60% by chemistry teachers and 89.60% by students